Enhancing higher-order thinking skills in chemical equilibrium through a game-based learning module - Rusli, Nurul Hanani; Ibrahim, Nor Hasniza; Md Aris, Norliyana (Eclética Química, 2025)
In 21st-century learning, higher-order thinking skills (HOTS) are essential for matriculation students. However, lacking HOTS materials gives students less opportunity to practice HOTS in chemistry. This research paper developed a game-based learning module based on the Revised Bloom's taxonomy and a game-based learning model. Pre-experimental design with a one-group pre-test and post-test was employed to measure the effects of the module on students' HOTS namely analyzing, evaluating, and creating thinking skills, involving 30 students at matriculation college. The result shows an increase in mean scores in post-test compared to pre-test scores and paired sample T-test shows a significant difference between pre-test and post-test scores with p<0.05. The findings contributed to the potential of game-based learning for promoting HOTS at the matriculation level and providing learners with a quality education.